Physical rehabilitation of patients with injuries of the anterior cruciate ligament of the knee in the postoperative period. - Davydenko E.V.; Gagara V.F. (Pedagogìka, Psihologìâ ta Mediko-bìologìčnì Problemi Fìzičnogo Vihovannâ ì Sportu, 2011)
The results of research to evaluate the effectiveness of influence on the organism of patients with knee ligament damage picked up a complex of methods of physical rehabilitation. The experiment involved 20 men aged 30-40 years with a complete rupture of the anterior cruciate ligament of the knee in the postoperative period. The study found that matched rehabilitation complex was more effective than traditional complexes, which are used in hospitals and rehabilitation institutions.